Multilingual Learner’s Thinking Rhetoric: Changes in Language Rhetorical Style - Raga Driyan Pratama (Langkawi: Journal of The Association for Arabic and English, 2018)
Language and cognition are interdependent elements which are currently relevant to second language acquisition issues. Learners will simultaneously acquire the thinking rhetoric carried out by a target language once they acquire the language itself. The externalization of the cognitive process can be seen from learner’s writing product or speaking performance that have been greatly investigated by numbers of researchers. The proposed problem was what happened to multilingual learner’s thinking rhetoric. Did they easily change between one language rhetorical styles to another? Or, their cognitive control mechanism was just intersected?  This study aims at reviewing the concept of multilingual learner’s thinking rhetoric along with their externalizations. It is expected that this study contributes to unlocking the dilemma of learners’ cognitive problems when acquiring multilanguage and initiating further research concerning how to handle multilingual learners’ language rhetorical styles.